Breakdowns of the chronology and sense: a narratological approach to From the Life of the Marionettes - Rodríguez Serrano, Aarón (2019)
The present article proposes an approach to one of the less studied films of the Swedish director Ingmar Bergman: From the life of the Marionettes (Aus dem Leben der Marionetten, 1980). We are particularly interested in the study of the filmic form and the traces of the enunciation as generators of meanings. Therefore, we will use a hybrid methodology that combines the structural analysis of the story with the application of formal microanalysis processes. We intend to demonstrate how strictly formal decisions respond intimately to the question of the meaning that triggers the drama and the complexity of the characters. We will divide the fields of analysis into three specific categories: the chronology of the diegesis (frictions between the time of the story and the time of the film), the system of narrators and the temporal management of the point of view (especially in the significant implications of flashbacks and flash-forwards).